Investigating the enrichment of health literacy through product labeling : a comprehensive case study on young adults in Klang Valley, Malaysia - Keith, Kittivongsak Vongsuthep (2023)
Health literacy has emerged as a progressively significant issue in the field of public health today. The term "Health literacy" is the degree to which individuals can obtain, process, and understand basic health information and services needed to make appropriate health decisions. Therefore, Health literacy is essential for everyone because, at some point in our lives, we all need to be able to find, understand, and use health information and services. Meanwhile, the term product labeling refers to the displaying of product information on its packaging. The label on a product lets the customers or consumers know what is in the food or product they use. It also lets the consumer know how healthy or unhealthy the product is. According to the survey conducted by the International Food Information Council (IFIC) Foundation and the American Heart Association, almost all Americans (95 per cent) report that they always or sometimes look for healthy options when food shopping. Consumers say they are more likely to consult food labels for healthfulness when buying a product for the first time. A small indication that product labeling contributes to promoting health literacy. Overall, Health literacy has proven to help us to prevent health problems, protect our health, and better manage health problems when they arise. The methodology that can be used is Qualitative research, collection and analysis of non-numerical data. For example, researchers can carry out interviews to obtain information or spoken word from the public to know whether they agree or disagree on whether product labeling on products can promote health literacy in local society. In short, at the end of this research study, one of the barriers of reaching health literacy through product labeling and was also found able and the effectiveness of product labeling in promoting health literacy were also examined. According to the data analysis in this research study, one of the barriers that hinders young adults from private universities within the Klang Valley health literacy in the context of product labeling is that reading nutrition labels takes too much time. Moreover, in this research study, it was discovered that the product labeling is effective in promoting health literacy among them as the majority of the respondents strongly agreed that they are concerned about their health and they try their best to only choose products that provide them detailed health information.